Violation of the Stokes–Einstein relation in Ge2Sb2Te5, GeTe, Ag4In3Sb67Te26, and Ge15Sb85, and its connection to fast crystallization. (15th August 2020) - Wei, Shuai; Persch, Christoph; Stolpe, Moritz; Evenson, Zach; Coleman, Garrett; Lucas, Pierre; Wuttig, Matthias
Abstract: Phase-change materials (PCMs) are already commercialized in optical and non-volatile memory devices. Yet, the dynamics of atomic rearrangement processes and their temperature dependence, which govern their ultrafast switching, are still not fully understood. Here we use quasi-elastic neutron scattering to investigate the liquid-state dynamics of four prevailing PCMs Ge2 Sb2 Te5, GeTe, Ag4 In3 Sb67 Te26 (AIST), and Ge15 Sb85 above their respective melting points Tm . Self-diffusion coefficients and structural relaxation times on the timescale of picoseconds are extracted from dynamic structure factors. The results indicate an unusual systematic violation of the Stokes-Einstein relation (SER) for each PCM in high-temperature regions above Tm, where the atomic-mobility is high. This is likely related to the formation of locally favored structures in liquid PCMs. Absolute values of diffusivity in the supercooled liquid AIST are derived from crystal-growth velocity, which are almost one order of magnitude higher than that expected from the SER in the technologically relevant temperature range ~20% below Tm . This is relevant to understand the crystallization kinetics of PCMs as crystal growth is controlled by diffusivity. Furthermore, the instantaneous shear modulus is determined ranging from 2 to 3 GPa for liquid PCMs, which permits extracting viscosity from microscopic structural relaxations usually accessible to simulations and scattering techniques. Graphical abstract: Image, graphical abstract